Experimental Study on Brucella abortus Strain RB51 Vaccinated Water Buffalo (Bubalus bubalis) Challenged with Virulent B. abortus Strain during Pregnancy - Adesiyun, Abiodun Adewale; Ramnanan, Anil; Campbell, Mervyn; Asgarali, Zinora; Diptee, Michael (Journal of Buffalo Science, 2018)
The study was conducted to determine the efficacy of Brucella abortus strain RB51 (RB51) vaccine in preventing abortion in pregnant water buffalo (Bubalus bubalis) experimentally challenged using the intravenous route, with a local pathogenic strain of B. abortus biovar 1 (Trinidad 1). Thirty-two female water buffalo calves aged 6-10 months were randomly divided into three groups for the vaccination trial using the subcutaneous route: Group I animals received recommended dose (RD) vaccine twice 4 weeks apart, Group II was vaccinated twice 18 weeks apart and Group III (control) received saline once. At approximately 6 months of pregnancy following natural breeding, the animals were challenged by the intravenous route with 2.5 x 108 to 4.4 x 108 colony forming units of a local strain of B. abortus, Trinidad 1. Blood samples were collected, pre-challenge and post-challenge, for serological assay using the BPAT and the animals were monitored for clinical signs. The bacteriological study was also performed on tissues of the dams and their calves. The frequency of abortion/stillbirths/early neonatal deaths was 55.6% (5/9), 42.9% (3/7) and 40.0% (2/5) for Groups I, II and III dams respectively (P>0.05; χ2). For calves from infected dams, the frequency of isolation of B. abortus Trinidad 1 from the abomasal and rectal swabs was 100.0%, 80.0% and 100.0% for Groups I, II and III animals respectively (P>0.05). It was concluded that vaccination of water buffalo with the RB51 vaccine using the recommended dose was ineffective in preventing infection, abortion, stillbirths, and neonatal deaths.